2020
DOI: 10.1016/j.hpb.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and network meta-analysis of different surgical approaches for pancreaticoduodenectomy

Abstract: Background: Minimally invasive pancreaticoduodenectomy (MIPD) is a demanding surgical procedure, thus explaining its slow expansion and limited popularity amongst Hepato-Pancreatico-Biliary (HPB) surgeons. However, three main advantages of robotic assisted pancreaticoduodenectomy (PD) including improved dexterity, 3D vision less surgical fatigue, may overcome some of the hurdles and ultimately lead to a wider adoption. This systematic review and network meta-analysis aims to evaluate the current literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 93 publications
(94 reference statements)
2
36
0
1
Order By: Relevance
“…Previous studies have showed that LapPD and RobPD seem to be equally safe and were associated with reduced morbidity, shorter hospital length of stay, and non-inferior oncologic outcomes when compared to OpenPD [9][10][11][12][13][14]. The purpose of this network meta-analysis is to provide an updated evidence comparing short-term surgical and oncologic outcomes within pure OpenPD, LapPD, and RobPD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have showed that LapPD and RobPD seem to be equally safe and were associated with reduced morbidity, shorter hospital length of stay, and non-inferior oncologic outcomes when compared to OpenPD [9][10][11][12][13][14]. The purpose of this network meta-analysis is to provide an updated evidence comparing short-term surgical and oncologic outcomes within pure OpenPD, LapPD, and RobPD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the theoretical and potential advantages that robotic surgery offers, its widespread use is limited by its high cost that has curtailed accessibility to the robotic platform. 8 Globally, only a few centres 4,15,31 have reported their experiences with RPS. The high cost of acquiring and maintaining this platform has meant that few surgeons from around the world have regular access to this technology for training purposes.…”
Section: Limitations Of Rpsmentioning
confidence: 99%
“…11 Compared to the open approach, LPS is reported to provide the added benefits of smaller incisions with better cosmetic results, lower level of postoperative pain and estimated blood loss, shorter hospital stay and recovery time with equivalent morbidity and overall mortality rate. [12][13][14][15][16][17][18] It is, however, important to emphasise that most of the evidence that supported the use of LPS is limited to retrospective case-control studies, [12][13][14][15][16][17][18] and only 4 randomised controlled trials (RCT) had been performed to date. [19][20][21][22] Despite the clinical advantages offered by LPS, the major obstacle to its widespread adoption is the technically demanding nature of the procedure and its steep learning curve.…”
Section: Introductionmentioning
confidence: 99%
“…To raise the rate of survival in PDAC patients, more financial costs have been made around the world ( 7 , 8 ). Currently, surgical treatment is still the only radical therapy for PDAC ( 9 , 10 ). Although adjuvant chemotherapy may prolong the survival of PDAC patients, the prognosis of PDAC patients remains poor due to the lack of early diagnostic methods and accurate recurrence and prognostic biomarkers ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%